Pelabelan Selimut Bintang Ajaib Super Pada Graf Bintang - Mattiro, N; Sudarsana, I W (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2021)
Let be a simple graph. An edge covering of is a family of subgraphs such that each edge of graph belongs to at least one of the , subgraphs. If each is isomorphic with the given graph , then it is said that contains a covering. The graph G contains a covering and the bijectif function is said an the magic labeling of a graph G if for each subgraph of is isomorphic to , so that is a constant. It is said that the graph G has a super magic if in this case, the graph G which can be labeled with magic is called the covering graph magic. A star graph with n points is a graph with points and sides, where point is degree and the other point has degree denoted by . This study aims to determine the presence of covering labeling for the super-magic star on the star graph. The research methodology is literature study. The results show that the star graph for has magic covering labeling with magic constants for all covering is and the super-magic covering labeling with magic constants for all covering is .